Development of a new solar system integrating photovoltaic and thermoelectric modules with paraffin-based nanomaterials - A. M. Alinia; M. Sheikholeslami (Scientific Reports)
Abstract This study investigates a comprehensive enhancement strategy for photovoltaic (PV) panel efficiency, focusing on increasing electrical output through the integration of parabolic reflectors, advanced cooling mechanisms, and thermoelectric generation. Parabolic reflectors are implemented in the system to maximize solar irradiance on the PV panel’s surface, while a specialized cooling system is introduced to regulate temperature distribution across the silicon layer. This cooling system consists of a finned duct filled with paraffin (RT35HC) and enhanced with SWCNT nanoparticles, which improve the thermal properties of the paraffin, facilitating more effective heat dissipation. The PV module is also integrated with a TEG (thermoelectric generator) to capture excess thermal energy and convert it into additional electrical power, allowing for a more efficient overall system. To simulate the heat flux introduced by the reflectors, SolTrace software was employed, while the unsteady, three-dimensional thermal behavior of the system was analyzed using ANSYS FLUENT. Simulated results demonstrated that, with the cooling system in place, the PV efficiency (ηel, PV) improves by approximately 16.46% in clean conditions. However, dust accumulation on the panel significantly impacts performance, reducing ηel, PV by around 46.48% after 60 min. The inclusion of fin structures further optimizes the system, boosting overall efficiency by approximately 6.77% in clean conditions and 3.78% under dust-affected conditions. Additionally, thermal efficiency for the clean state increased by about 8.47% due to the fins. Notably, the combined effects of parabolic reflectors, fin-enhanced cooling, and TEG integration yield an electrical output power approximately 2.94 times greater than that of a PV panel without any reflector or cooling modifications.